MODELING INFORMATION SYSTEM FOR AGROINDUSTRY OF JAMU MADURA - Khoirul Hidayat (Teknika: Engineering and Sains Journal, 2018)
Jamu Payung Emas Siti Fatma vepretty much mastered the markets, especially in the area of East Java. With the development of Jamu Payung Emas Siti Fatma industry, the required data processing system more regularly so as to facilitate the herbal medicine industry is in a store all the information related to the production. Therefore, it is necessary to do research on agro-industry system design information Jamu Madura. This research method using system development life cyrcle (SDLC) method.  Preparation and storage database, using a MySQL the programming language used is PHP and interface design was created using LTE Admin Template the editor is Sublime Text. The results of this study indicate that the design of information systems agroindustrial of Jamu Madura require ten entities are tables on leave, the employee table, the table stops working, the product table, table sales detail, table salaries, tables other expenses, entry table another table the bill of sale, and the table notes production. Each entity has a data type that has been tailored to the needs of data and linked with other entities that have relevance to make the system completely. Ten of these entities then designed and built the system up into four modules, namely modules personnel (containing sub-modules of employees, submodule salaries, submodule off, and submodule stops working), production modules (containing submodule products and submodule production records), marketing modules (containing submodules, and submodules sales note monthly demand), and the financial module (submodule contains other income and other expenses submodules). In each submodule, there are several actions that menu adds, edit, delete, and print so that users can monitor and control the company's system more easily.